Critique of Yakov Zeldovich’s “The Theory of Ignition by a Heated Surface”: Self-Ignition of an Infinite Combustible by Heated Bodies - Filippov, A. A. (Doklady. a journal of the Russian Academy of Sciences. Physics, 2023)
The basic principles of a thermal explosion had been studied and published by 1980. It seemed that the research was completed, but later it was discovered that Zeldovich’s “ignition condition” does not correlate with the experimental data. “The theory of ignition by a heated surface” is the basis of ignition theory, but, although the calculations are correct, the results obtained are mistakenly attributed to ignition—in reality they describe the spontaneous ignition of an infinite combustible. Our work shows that a thermal explosion of a combustible from a heated body can develop as ignition and self-ignition. The conditions for self-ignition of an infinite combustible by a flat surface and a cylinder are given, as is the likely condition for the ignition of a combustible between parallel walls of different temperatures.